2021
DOI: 10.1016/j.jcot.2020.08.010
|View full text |Cite
|
Sign up to set email alerts
|

YouTube – An unreliable source of information for Total hip replacement

Abstract: Background: YouTube is now becoming important for people as a source of health related information. The aim of the present study was to assess the educational quality of YouTube videos related to Total hip replacement. Methods: A search on YouTube for the term "Total hip replacement" was performed. Data from 47 most relevant videos were collected. Quality assessment checklists with a scale of 0e10 points were developed to evaluate the video content. Videos were grouped into poor quality (grade 0e3), acceptable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…Previous research suggests that low-quality medical information obtained on YouTube harms the relationship between a doctor and his/her patients 20 . Based on many publications evaluating the quality of videos on various orthopaedic diseases, we concluded that the videos' accuracy and quality were low [21][22][23][24][25][26][27] .…”
Section: Discussionmentioning
confidence: 95%
“…Previous research suggests that low-quality medical information obtained on YouTube harms the relationship between a doctor and his/her patients 20 . Based on many publications evaluating the quality of videos on various orthopaedic diseases, we concluded that the videos' accuracy and quality were low [21][22][23][24][25][26][27] .…”
Section: Discussionmentioning
confidence: 95%
“…Since YouTube has shown to be a poor source for general meniscal information, and our study showcases it as a poor source for meniscus tear rehabilitation, it is an unreliable source for medical information on meniscus injuries and management [ 22 ]. Not only is YouTube a poor source for meniscal information, but it has also been shown to be a poor source for hip arthroscopy, ACLR, or total hip replacement information [ 6 , 16 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The AFCS is built upon a foundation of patient-oriented information from reputable sources such as the Orthopaedic Trauma Association (OTA), the American Academy of Orthopaedic Surgeons (AAOS), the American Podiatric Medical Association (APMA), the American Orthopaedic Foot & Ankle Society (AOFAS), and the American College of Foot and Ankle Surgeons (ACFAS). The comprehensive nature of this source material ensures the scoring system is both comprehensive and reflective of current standards in patient education regarding ankle fractures [ 9 , 14 ].…”
Section: Methodsmentioning
confidence: 99%